2021
DOI: 10.3390/toxics10010002
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Formation of Chemical–Hemoglobin Adducts

Abstract: Hemoglobin (Hb) adducts have been used as biomarkers for the internal exposure to chemicals. Simultaneous exposure to chemicals that bond with the N-terminal valine of Hb to form adducts, such as glycidol, acrylamide, and glucose, may affect the formation of the individual Hb adducts. In this study, various factors influencing the formation of chemical–Hb adducts were analyzed using in vitro and in vivo systems. In the in vitro assays, the formation of glycidol– and acrylamide–Hb adducts was altered in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Glycidol administration to mice or rats resulted in the formation of a hydroxypropanoic acid valine adduct ( m/z 577) from glycidic acid, a minor metabolite of glycidol (Vryonidis et al., 2022 ). Furthermore, our previous study showed that acrylamide or glucose can affect the formation of diHOPrVal (Shimamura et al., 2022 ). Thus, the effect of combined exposure to various chemicals in food and the environment may also affect the formation of diHOPrVal, a marker of glycidol.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Glycidol administration to mice or rats resulted in the formation of a hydroxypropanoic acid valine adduct ( m/z 577) from glycidic acid, a minor metabolite of glycidol (Vryonidis et al., 2022 ). Furthermore, our previous study showed that acrylamide or glucose can affect the formation of diHOPrVal (Shimamura et al., 2022 ). Thus, the effect of combined exposure to various chemicals in food and the environment may also affect the formation of diHOPrVal, a marker of glycidol.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, our previous study showed that acrylamide or glucose can affect the formation of diHOPrVal (Shimamura et al, 2022).…”
Section: Dihoprval Production In Mice After Repeated Oral Administrat...mentioning
confidence: 96%
“…Although several factors influencing the Hb adduct formation have been investigated [ 32 ], the contribution of lipase activity has not been evaluated. The bioavailability of glycidol from GEs have been evaluated in rats, and the amount of diHOPrVal in the blood was equivalent between groups receiving equimolar doses of glycidol or glycidyl palmitate esters [ 33 ].…”
Section: Discussionmentioning
confidence: 99%